Crab Species-Specific Excavation and Architecture of Burrows in Restored Mangrove Habitat - Wah Wah Min; Kathiresan Kandasamy; Balasubramaniyan Balakrishnan (Journal of Marine Science and Engineering, 2023)
Burrowing crabs are considered to be ecosystem engineers, playing a vital role in mangrove ecosystems through bio-geochemical transformation. This process depends on the size and shape of burrows. The present study analyzes the architecture of burrows constructed by crabs in a restored mangrove habitat. Fourteen crab species were found to construct burrows of 13 different shapes, with a predominance of I-, J-, and L-shapes. Sesarmids were larger in size than fiddlers, and made burrows with wider openings mostly in the Rhizophora zone. Fiddlers constructed complex burrows with a vertical position, and made longer and deeper burrows in contrast to sesarmids, which formed simple burrows with a horizontal position, digging shorter and shallower burrows in Avicennia or open zones. The sesarmids had smaller burrows without branching in mangrove zones, whereas the fiddlers had larger burrows with or without branching in open and Avicennia zones. The burrows of fiddler crabs, especially Austruca occidentalis and A. annulipes, had separate openings and passages for exit and entry as an adaptation against predators. The present work identified Austruca occidentalis and A. annulipes as the most potent bioturbating crab species in restored mangrove habitats due to their efficiency in soil excavation and formation of large-sized burrows.